Comparison of Serological Methods with PCR-based Methods for the Diagnosis of Community-acquired Pneumonia Caused by Atypical Bacteria (2016)
ABSTRACT: The diagnosis of community-acquired pneumonia (CAP) caused by Legionella pneumophila, Mycoplasma pneumoniae, and Chlamydophila pneumoniae is traditionally based on cultures and serology, which have special requirements, are time-consuming, and offer delayed results that limit their clinical usefulness of these techniques. We sought to develop a multiplex PCR (mPCR) method to diagnosis these bacterial infections in CAP patients and to compare the diagnostic yields obtained from mPCR of nasopharyngeal aspirates (NPAs), nasopharyngeal swabs (NPSs), and induced sputum (IS) with those obtained with specifc PCR commercial kits, paired serology, and urinary antigen. Results: A total of 225 persons were included. Of these, 10 patients showed serological evidence of L. pneumophila infection, 30 of M. pneumoniae, and 18 of C. pneumoniae; 20 individuals showed no CAP. The sensitivities were mPCR-NPS = 23.1 %, mPCR-IS = 57.1 %, Seeplex®-IS = 52.4 %, and Speed-oligo®-NPA/NPS = 11.1 %, and the specificities were mPCR-NPS = 97.1 %, mPCR-IS = 77.8 %, Seeplex®-IS = 92.6 %, and Speed-oligo®-NPA/NPS = 96.1 %. The concordance between tests was poor (kappa <0.4), except for the concordance between mPCR and the commercial kit in IS (0.67). In individuals with no evidence of CAP, positive reactions were observed in paired serology and in all PCRs.Conclusions: All PCRs had good specificity but low sensitivity in nasopharyngeal samples. The sensitivity of mPCR and Seeplex® in IS was approximately 60 %; thus, better diagnostic techniques for these three bacteria are required. Keywords: M. pneumoniae, L. pneumophila, C. pneumoniae, Multiplex PCR, Atypical pneumonia, Molecular diagnosis